The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s0006-87052006000300009
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência da poda em cafeeiros no controle da Xylella fastidiosa

Abstract: A bactéria Xylella fastidiosa coloniza os vasos do xilema dos seus hospedeiros, bloqueando o movimento da água e nutrientes, afetando a produção. Até o momento, o manejo adequado do cafezal, desde o plantio, com o uso de mudas isentas da bactéria e o controle das cigarrinhas vetoras, são medidas que atenuam a incidência da doença. A poda é uma prática importante para a otimização da produção do cafezal, e o tipo de poda depende da cultivar e do ambiente, usando-se podas tradicionais ou drásticas. Neste trabalh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Furthermore, it can encourage the growth of new, uninfected branches. This method has already been tested on oleanders [80], citrus [81], coffee [82], grapevine [83,84], almond trees [85], and olive trees [15]. However, according to Bucci et al, there is no conclusive evidence of the effect of pruning on containing any of the diseases caused by Xf [86].…”
Section: Control Of Infected Plantsmentioning
confidence: 99%
“…Furthermore, it can encourage the growth of new, uninfected branches. This method has already been tested on oleanders [80], citrus [81], coffee [82], grapevine [83,84], almond trees [85], and olive trees [15]. However, according to Bucci et al, there is no conclusive evidence of the effect of pruning on containing any of the diseases caused by Xf [86].…”
Section: Control Of Infected Plantsmentioning
confidence: 99%
“…A few reports conducted under field conditions in the Brazilian state of São Paulo indicate variation in the level of infection among C. arabica cultivars, C. liberica varieties and their interspecific hybrids. For instance, it was observed that Acaiá IAC 474‐19 was less severely affected by the disease than Catuaí Vermelho IAC 81 in Campinas (Queiroz‐Voltan et al ., ); cultivars Catuaí and Mundo Novo showed more disease severity than other commercial cultivars in Mococa, particularly during rainy periods (Queiroz‐Voltan et al ., ). Accessions of C. liberica var.…”
Section: Coffee Leaf Scorchmentioning
confidence: 99%
“…Chemical treatment in areas with history of the disease usually involves preventive application of copper-based compounds alone or in mixtures with mancozeb (and insecticides in the case of X. fastidiosa) sometimes in alternation with kasugamycin (Zambolim et al, 2005;Patr ıcio et al, 2010;Patr ıcio & Oliveira, 2014). In the case of X. fastidiosa, severe pruning has also been proposed as an efficient alternative to control the disease (Queiroz-Voltan et al, 2006;Rocha et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%